“Syair Perang Mengkasar”: antara Otensitas Sejarah, Transformasi Emosi, dan Eksistensi Komunitas Melayu di Gowa - Ahyar Anwar (Humaniora, 2009)
Syair Perang Mengkasar is a manuscript written by Encik Amin, a Malayan men of letters, who stayed in Kingdom of Gowa in the seventh century. Its text position is too dialectic with Makassarese Battle held between 1666 until 1669 and involved the kingdoms of Gowa and Bone with it's ally, VOC led by Speelman. There are three fundamental aspects in Syair Perang Mengkasar manuscript. They were historical authenticity, emotional transformation, and the existence of Malayan community in the history of Gowa kingdom. Those three aspects have became the basic analysis in understanding the position of Syair Perang Mengkasar manuscript in history escalation and the complexity of Perang Mengkasar incident.